Industrial Relations Policy through Human Development and Talent Management during Tourism Occupancy Decline in Bali on Employee Well-Being - Desak Komang Febrianita; Budi Santoso (PT. Anagata Sembagi Education, 2026)
The decline in occupancy within Bali’s tourism industry has created significant pressure on organizations to adapt their industrial relations policies alongside human development and talent management (HD&TM) strategies in order to sustain employee well-being. Fluctuations in tourist arrivals not only affect company revenues, but also influence employment stability, work intensity, and psychological security among hospitality workers. According to the International Labour Organization, periods of economic uncertainty in tourism-dependent regions often lead to increased job insecurity and deteriorating working conditions if not managed through inclusive industrial relations frameworks. This study aims to analyze how the integration of industrial relations policies with HD&TM practices influences employee well-being in the Bali tourism sector. Industrial relations that emphasize fairness, transparency, and employee participation play a crucial role in maintaining trust between management and workers, particularly during periods of organizational restructuring. When such policies are aligned with structured human development initiatives such as continuous training, career planning, and talent retention programs organizations are better positioned to safeguard employee engagement and psychological well-being. The findings indicate that fair, transparent, and participatory industrial relations supported by systematic HD&TM practices enhance employee engagement, loyalty, and overall well-being, while simultaneously reducing turnover intention. This is consistent with Gallup’s (2023) report, which highlights that employees who perceive their organization as supportive of development and fair treatment are significantly more likely to demonstrate higher commitment and lower intention to leave. Therefore, the integration of industrial relations and HD&TM strategies is not merely a compliance mechanism, but a strategic approach to sustaining workforce resilience and organizational performance in Bali’s tourism industry.